see the both photos for answer
Well if the first point is (-2, 1) and the slope is three than the other point would be (-1, 4)
Answer:
37.6991
Step-by-step explanation:
Answer:
Ohhh ok No problem i will accept it
What I would do here is substitute "5y -87" for x in the first ecquation, since the second equation is already in the form "x=..." so:
4*(5y-87)+9y=29
getting rid of the bracket:
20y-348+9y=29
adding up:
29y=29+348
29y= 377
dividing by 29:
y=13
and now we can calculate x, which is 5*13-87=65-87=-22
so x=-22